Remote pilot modelling for evaluation of ACAS Xu - Stroeve, S.H.; Villanueva-Cañizares, C.J.; Dean, G. (SESAR Joint Undertaking, 2023)
A remote pilot (RP) model is developed for evaluation of unmanned aircraft (UA) manoeuvring in response to remain well clear guidance and resolution advisories by the ACAS Xu detect-and-avoid system. The model describes RP situation awareness, decisions, response modes, delays, strengths and flight control in deterministic and stochastic settings. It is integrated in a simulation environment that describes sets of aircraft and their sensing systems. Simulation results illustrate the impact and complexity of UA manoeuvring by RPs for ACAS Xu advices.